Characterization of blood microbial population in beef calves with clinical signs of sepsis using 16S rRNA gene sequencing - Giuliano Borriello; Flaminia Valentini; Sara Ferrini; Giorgia Di Muro; Giulia Cagnotti; Elena Grego; Angela Maria Catania; Maria Cristina Stella; Ugo Ala; Patrizia Nebbia; Antonio D’Angelo; Claudio Bellino (PLoS ONE, 2025)
Sepsis, a dysregulated host response to infection, severely affects calf health. To date, sepsis diagnosis relies on clinical examination and positive blood culture. Differently, in humans 16S rRNA gene analysis is a valuable adjunct to blood culture as it allows for broader assessment of bacterial DNA in whole blood and its fractions. However, its efficacy in cattle remains unknown. Therefore, this study characterized and compared the bacterial DNA detected in whole blood and its fractions between healthy calves and those showing clinical signs of sepsis. The study sample was 18 Piedmontese calves classified according to their clinical status as suspected septic (S, 8/18) or healthy (H, 10/18). Aseptic blood samples were collected into EDTA tubes for 16S rRNA gene analysis of whole blood (WB), plasma (PL), buffy coat (BC), and red blood cells (RBC). Aseptic samples were additionally taken only from the S calves for blood culture. Clinical and microbiological parameters were compared between the two groups and between the blood fractions within each group. The S calves were diagnosed with pneumonia (3/8, 37.5%), enteritis (3/8, 37.5%), and omphalitis (2/8, 25%). Microbiome analysis revealed significant intra-group differences in α and β diversity indices between PL and the other blood fractions for both groups. Comparison between the S and the H calves showed differences in β diversity indices for PL and WB. DNA of known pathogens (e.g., Escherichia coli) and species not commonly associated with sepsis (e.g., Cutibacterium acnes) were more abundant in the S calves. Moreover, in S calves, 16S rRNA gene sequencing detected E. coli DNA more often (8/8, 100%) than blood culture (2/8, 25%). While the DNA of several bacteria can be detected in calves showing clinical signs of sepsis, further studies are needed to clarify its origin, role, and distribution in blood fractions.